Evaluation Of Child Friendly Pesantren Program In West Sumatra Province - Albert; Zulmuqim; Iswantir; Irwandi; Aulia Rahman (al-Afkar, Journal For Islamic Studies, 2023)
This research  describes the results of the evaluation of the child-friendly Pesantren program in West Sumatra Province. The model used by CIPP is the Mixed Method. Data collection techniques used questionnaires, observation sheets, interviews, concept mastery tests and guidelines for child-friendly Islamic boarding schools. Data analysis and program evaluation procedures are described in this article. The results of the context evaluation show that violence, discrimination and harassment still occur in the average Islamic boarding school in the province of West Sumatra. The results of the input evaluation show that the guidelines for the child-friendly pesantren program issued by the Ministry of Religion, the Ministry of Women's Empowerment and Child Protection of the Republic of Indonesia have not been optimally socialized and the pesantren leaders, asatidz councils, students and the community are aware of the existence of a child-friendly pesantren program but do not yet understand the concepts, guidelines and technical instructions for child-friendly pesantren. The results of the process evaluation, namely monitoring designed to reveal the strengths and weaknesses of the implementation of the child-friendly Islamic boarding school program have not been optimal. Not all Islamic boarding schools have a child-friendly boarding school development team. For pesantren that already have a child-friendly pesantren team, the team members do not yet have the relevant competencies. Evaluation of products or outputs and results designed to assess program results and program sustainability shows that the child-friendly Islamic boarding schools program launched and developed by the government and Islamic boarding schools have not run as expected.